Distal Positioning of the Ulnar Shortening Plate Increases Symptomatic Removal: A Comparative Analysis of Ulnar Shortening Osteotomy Plate Positioning and Symptomatic Hardware Removal - Hoy, John F.; Smith, Shelby R.; Hanson, Zachary C.; Fernandez, John J.; Simcock, Xavier C. (Journal of Wrist Surgery, 2024)
Ulnar shortening osteotomy (USO) is a common procedure to treat symptomatic ulnar-sided wrist symptoms in patients with positive ulnar variance who fail nonoperative management. Plate placement on the volar, dorsal, or subcutaneous border of the ulna has been described. There remains debate regarding the optimal plate placement to minimize soft tissue irritation and the need for plate removal. The goal of this study is to determine whether plate position along the volar cortex versus along the subcutaneous border, as well as the distance of the plate from the ulnar styloid, affects the risk of symptomatic hardware requiring removal.In total, 112 USO procedures on 107 patients performed between 2017 and 2023 were retrospectively reviewed. The position of the plate on the ulna and the distance of the plate from the ulnar styloid were assessed radiographically. Demographic information, visual analog scale pain scores, disability of the arm, shoulder, and hand scores, and incidence of hardware removal were collected and compared between plate location groups.The overall symptomatic hardware removal rate was 79%. There was no difference in the rate of symptomatic hardware removal between volar (80%) and subcutaneous (77%) plate locations (p = 0.69) at a mean follow-up time of 26 months. The mean distance from the distal plate to the ulnar styloid was higher in cases in which hardware was retained (p = 0.03).We found no difference in hardware removal rates based on volar versus subcutaneous plate placement after USO. Cases in which hardware was not removed had a higher mean distance from the distal plate to the ulnar styloid. Further prospective studies are warranted to determine optimal plate positioning to minimize hardware irritation after USO.
Keywords: ulnar shortening osteotomy; hardware irritation; hardware removal; ulnar impaction syndrome